(untitled) (American International Journal of Economics and Finance Research, 2023)
Money laundering has recently become a global threat, impacting developed and poor countries. In developing countries like Bangladesh, it is more difficult to combat financial crime than in developing countries because of the inadequate regulatory environment and vulnerable financial system. Bangladesh’s central bank issues guidelines to facilitate the implementation of the Prevention of money laundering act. According to the guideline of Bangladesh Bank, all financial institutions must develop anti-money laundering policies to ensure the safety and soundness of their institutions. This study aims to focus on the role of authorized agencies in combating money laundering. In this paper, the latest trends in financial crimes have been discussed from Bangladesh’s perspective. The preventive measures for money laundering and other financial crimes have been discussed elaborately. So far, money laundering is a sophisticated and dynamic crime; the criminals continuously took innovative processes to use the financial system to launder money. Hence, the challenges of authorized agencies are crucial to combat money laundering. The study will take a step in pointing out the role and challenges of the authorized agencies in combatting money laundering in Bangladesh. JEL Classification Codes: K42.